Boredom at work: Work Psychology’s recent contributions - Solf Zárate, Arturo (2018)
This paper is related to the experience of boredom of personnel in workplaces, as well as its consequences. The contributions of empirical research, which has recently increased against the evidence of a continuous rise of that state, are emphasizedThe text includes aspects such as: definition, characteristics, measurement, and process analysis. Then, there are some suggestions to carry out future researches on the subject. Finally,practical guidelines are presented for its prevention or diminution.